Research complex linac-300 upgrade project and the lines of nuclear research - Buki, A.Yu.; Dovbnya, A.N.; Gokov, S.P.; Kasilov, V.I.; Kochetov, S.S.; Kushnir, V.A.; Mitrochenko, V.V.; Makhnenko, L.A.; Makhnenko, P.L.; Nikitina, T.F.; Shevchenko, N.G.; Shopen, O.A. (Вопросы атомной науки и техники, 2009)
The paper describes the problems of upgrading the research complex LINAC-300 and the program of physical studies expected to be performed at it. The acceleration complex LINAC-300 includes three electron beam ejection channels, the beam translation system and the spectrometer SP-95. Some special features of already upgraded systems of the complex LINAC-300 are considered in detail, as well as the plan of activities for its further modernization is given together with the expected electron beam characteristics. Special attention is paid to the program of physical investigations that are underway or expected to be performed at the experimental complex.